PERBEDAAN ASUPAN ENERGI, PROTEIN DAN STATUS GIZI ANAK USIA PRA SEKOLAH DI SEKOLAH DENGAN MODEL SCHOOL FEEDING DAN NON SCHOOL FEEDING - Sunarti, . (Universitas Ahmad Dahlan, 2013)
ABSTRACTBackground: Common problem in pre school children is macronutrien and micronutrien defisiensi. In Indonesia, prevalention of severely undernutrition is 8,3 %, and moderate undernutrition is 27.5%. Prevalention of stunted are 46.6 % for boys in Indonesia and 45.5% for girls in Indonesia. Increasing trend of full day school model for pre school children with school feeding gives positif contribution by increasing children nutritional status. The objective of this research was to compare the difference of energy intake, protein intake and nutritional status of pre school children with school feeding and non school feeding model.Methods: The reseach design was cross sectional study that assesed variables in one point in time.Results: This results showed that there were differences of energy intake, protein intake and nutritional status (z-score) of pre school children with school feeding and non school feeding model with p value 0.000. Conclution: There were differences of energy intake, protein intake and nutritional status (z-score) of pre school children with school feeding and non school feeding model. Key word : nutritional status, school feeding, pre school ABSTRAKLatar belakang: Permasalahan umum yang dialami anak usia pra sekolah di Indonesia adalah defisiensi gizi, baik makronutrient maupun mikronutrien. Prevalensi gizi buruk pada anak usia pra sekolah sebesar 8,3% dan gizi kurang sebesar 27,5%. Prevalensi stunting sebesar 46,6% untuk laki-laki di Indonesia dan 45,5% untuk perempuan di Indonesia. Maraknya model pendidikan usia dini dengan pendekatan full day school sesungguhnya memberikan kontribusi yang positif terhadap peningkatan status gizi anak usia pra sekolah. Tujuan dari penelitian ini adalah untuk membandingkan perbedaan asupan energi, protein, dan status gizi anak usia pra sekolah dengan model school feeding dan non school feeding.Metode: Penelitian ini menggunakan desain cross sectional, dimana variabel diteliti dalam satu titik waktu.Hasil: Hasil ini menunjukkan adanya perbedaan asupan energi, protein, dan status gizi (z-score) anak usia pra sekolah dengan model school feeding dan non school feeding yaitu dengan p value sebesar 0,000.Kesimpulan: Ada perbedaan asupan energi, protein, dan status gizi (z-score) anak usia pra sekolah dengan model school feeding dan non school feeding. Kata kunci: status gizi, school feeding, pra sekolah